DETERMINAN MINAT BERTRANSAKSI MENGGUNAKANAN FINANCIAL TECHNOLOGY - Wardana, Ovi Rizki; Aliyah, Siti; Yanto, Yanto (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2024)
This study aims to determine the effect of perceived convenience, risk, attitude, subjective norms, knowledge, benefits and trust on interest in transacting using financial technology. This research is a quantitative research with data collection techniques using questionnaires to undergraduate students at UNISNU Jepara. The population in this study were undergraduate students at UNISNU Jepara. The sampling method in this study was simple random sampling method because the population size was known and the researcher used the slovin formula to determine the sample size for use in this study, namely a total sample of 98 students. The results showed that Perceived Convenience, Risk, Attitudes, Subjective Norms, and Trust had a positive effect on Interest in transacting using fintech among UNISNU Jepara students. While Risk, Effectiveness, Knowledge, and Benefits have no effect on Interest in transacting using fintech for UNISNU Jepara Students. The value of the coefficient of determination is 0.975. This explains that 97.5% of the variation in Interest in Transactions Using Financial technology can be explained through this regression. While the remaining 2.5% is explained by other variables outside of this study.